HUBUNGAN PEMBELAJARAN ONLINE DENGAN MOTIVASI BELAJAR SISWA KELAS V SD NEGERI 12 MANURUNGE KECAMATAN TANETE RIATTANG KABUPATEN BONE - ade sahvira; Abd Hafid; Sudirman Sudirman (JPPSD:Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
The problem in this research is the lack of student motivation towards online learning. This research is a quantitative study with a correlation design which aims to determine 1. the description of the online learning process at SD Negeri 12 Manuruge, the relationship between online learning and the learning motivation of fifth grade students at SD Negeri 12 Manuruge. 2. An overview of the learning motivation of fifth grade students at SD Negeri 12 Manuruge. 3. The relationship between online learning and learning motivation of fifth grade students at SD Negeri 12 Manuruge. The results showed that there was a significant relationship between online learning and the learning motivation of fifth grade students at SD 12 Manuruge with a thitung value (4.1375) greater (>) ttable value (0.671953) which means H0 is rejected and H1 is accepted. Based on the analysis of the data above, it can be concluded that the online learning process will have an impact on the mindset of students in learning so that it will affect their learning motivation in the classroom. So, the better the online learning process, the better the students' learning motivation.